2020
DOI: 10.18280/ijht.380126
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Analysis of Mist Injection and Water Shower Indirect Evaporative Cooling in Harsh Climate

Abstract: An experimental investigation of the performance of a direct-indirect evaporative cooling fresh air handling unit with different modes of operation is presented. Linear regression analysis is used to fit the experimental results, and the correlation coefficient is evaluated. It is found that the highest temperature reduction of 18.8℃ is achieved across the heat exchanger for the tested unit when the water shower mode is implemented at an ambient dry-bulb temperature of 44℃ in conditions of relative humidity le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…With a 25% reduction in condenser fan speed, the COP values were 4.86 and 4.77 for the top and middle nozzle locations. Additionally, reducing the fan speed further by 50% yielded COPs of 4.78 [15]- [17] and 4.72 for the same 3 upper and middle nozzle configurations. From these experimental results, it can be concluded that supplementing the condenser with 3 evaporative cooling nozzles leads to significant COP improvements, even when the condenser fan speed is reduced by up to 50%.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…With a 25% reduction in condenser fan speed, the COP values were 4.86 and 4.77 for the top and middle nozzle locations. Additionally, reducing the fan speed further by 50% yielded COPs of 4.78 [15]- [17] and 4.72 for the same 3 upper and middle nozzle configurations. From these experimental results, it can be concluded that supplementing the condenser with 3 evaporative cooling nozzles leads to significant COP improvements, even when the condenser fan speed is reduced by up to 50%.…”
Section: Resultsmentioning
confidence: 92%
“…Effective design is crucial for the successful implementation of evaporative cooling systems. Factors such as air velocity, wet-bulb temperature, and water distribution play pivotal roles in optimizing system performance [15]. This section outlines the key considerations in designing evaporative cooling systems, including the selection of materials, control mechanisms, and integration with existing HVAC systems.…”
Section: Resultsmentioning
confidence: 99%